Analysis approaches to construction of arithmetic coprocessors for problems of elliptic cryptography - Michail Grigorievich Babenko; Natalia Nikolaevna Vershkova; Nikolaj Nikolaevich Kucherov (Наука. Инновации. Технологии, 2022)
The article analyzes the methods of finding residue on a large prime modulus and describes an algorithm developed by the authors of the operation to find the residue of a large simple module in the system of residual classes using the approximate method of performing non-modular operations.